An Insufficient Preoperative Diagnosis of Borrmann Type 4 Gastric Cancer in Spite of EMR - Ahn, Jae Bong (The Korean Gastric Cancer Association, 2011)
Borrmann type 4 gastric cancers are notorious for the difficulty of finding cancer cells in the biopsy samples obtained from gastrofiberscopy. It is important to obtain the biopsy results for making surgical decisions. In cases with Borrmann type 4 gastric cancer, even though the radiological findings (such as an upper gastrointestinal series, abdominal computed tomography and positron emission tomography/computed tomography) or the macroscopic findings of a gastrofiberscopy examination imply a high suspicion of cancer, there can be difficulty in getting the definite pathologic results despite multiple biopsies. In these cases, we have performed endoscopic mucosal resection under gastrofiberscopy as an alternative to simple biopsies. Here we report on a case in which no cancer cells were found even in the endoscopic mucosal resection specimen, but the radiologic evidence and clinical findings were highly suspicious for gastric cancer. The patient finally underwent total gastrectomy with lymph node resection, and she was pathologically diagnosed as having stage IV gastric cancer postoperatively.